Color bar parameters for sdtv and hdtv systems - Гофайзен, Олег Вікторович; Алі, Мохаммед Хасан Хессейн; Пилявський, Володимир Васильович (Eastern-European Journal of Enterprise Technologies, 2011)
The model of color bar signals is presented for use for digital television video paths performance control. The set of parameters of these signals is offered for SDTV and HDTV standards with arbitrary bit depth of the quantized presentation for sampling formats of 4:2:2 and 4:4:4